Experimental Investigation of Friction Coefficient and Wear Rate of Stainless Steel 304 Sliding against Smooth and Rough Mild Steel Counterfaces - Chowdhury, M. A.; Nuruzzaman, D. M.; Roy, Biplov Kumar (GU J Sci, 2013)
In the present study, friction coefficient and wear rate of stainless steel 304 (SS 304) sliding against mild steel are investigated experimentally. In order to do so, a pin on disc apparatus is designed and fabricated. Experiments are carried out when smooth or rough mild steel pin slides on SS 304 disc. Experiments are conducted at normal load 10, 15 and 20 N, sliding velocity 1, 1.5 and 2 m/s and relative humidity 70%. Variations of friction coefficient with the duration of rubbing at different normal loads and sliding velocities are investigated. Results show that friction coefficient is influenced by duration of rubbing, normal load and sliding velocity. In general, friction coefficient increases for a certain duration of rubbing and after that it remains constant for the rest of the experimental time. The obtained results reveal that friction coefficient decreases with the increase in normal load for SS 304 mating with smooth or rough mild steel counterface. On the other hand, it is also found that friction coefficient increases with the increase in sliding velocity. Moreover, wear rate increases with the increase in normal load and sliding velocity. The magnitudes of friction coefficient and wear rate are different depending on sliding velocity and normal load for both smooth and rough counterface pin materials.